Stereotypical representations of the accountant in The New Yorker cartoons through time. Issue 4 (7th August 2020) - Blaber, Zlatinka N.; Brady, Donald L.; Gougoumanova, Guergana N.
Abstract : This article explores the accountant imagery in the cartoons of The New Yorker magazine from 1960 through 2018. The purpose of this study is: first, to determine what stereotypical representations of the accountant are portrayed in the magazine's cartoons; and second, to determine whether these representations conform to the cultural changes reported in previous studies – a movement from professionalism to commercialism. Five observations result from the cartoon data collected from The Cartoon Bank (TCB) and then eight hypotheses are tested. Z tests indicate that the frequency of cartoons depicting professionalism was statistically larger during the time periods 1960–1979 and 1990–1999. However, the frequency switched during the time periods 2000–2009 and 2010–2018 to depictions of commercialism being statistically larger. Therefore, the primary inference that can be drawn from this study is that the cultural change in the role of the accountant from professionalism to commercialism reported in the literature has been confirmed in the context of the accountant cartoons printed in The New Yorker between 1960 and 2018. Another conclusion drawn from this study is that the most prominent stereotypical representations of the accountant in The New Yorker cartoons are 'reputable' and 'uninteresting' (for cartoons depicting professionalism) and 'corrupt' and 'advice giver' (for cartoons depicting commercialism). Apparently, the cartoonists tend to think of accountants in terms of these stereotypes more so than the other stereotype categories examined. Interestingly, 'reputable' and 'advice giver' are effectively positive perceptions, while 'uninteresting' and 'corrupt' convey negative perceptions. Thus, the depiction of the temporal change of the accountant is not one of positive perceptions changing into negative perceptions with time. Even though the accounting scandals of the early 2000s are considered an ignominy for the accounting profession ('corrupt' stereotype), the social and professional status of accountants has not been entirely shrouded in negative portrayals.